Direct Immunofluorescence of Mechanobullous Epidermolysis Bullosa Acquisita, Porphyria Cutanea Tarda and Pseudoporphyria - Heleen J. de Groot; Marcel F. Jonkman; Hendri H. Pas; Gilles F.H. Diercks (Acta Dermato-Venereologica, 2018)

(untitled)
Mechanobullous epidermolysis bullosa acquisita (mEBA) can have a clinical presentation that is very similar to other blistering diseases, such as porphyria cutanea tarda (PCT) and pseudoporphyria. Direct immunofluorescence is an important feature in the diagnosis of mEBA, although features that overlap with PCT and pseudoporphyria have been reported. This retrospective observational study investigated whether direct immunofluorescence can discriminate mEBA from PCT and pseudoporphyria. Biopsies of 13 patients with mEBA, 10 with PCT and 10 with pseudoporphyria were included. In 7 cases of PCT and 4 of pseudoporphyria, direct immunofluorescence showed a pattern at the dermal–epidermal junction that appeared similar to the u-serrated pattern in mEBA. Vessel wall depositions were observed in all 3 diseases, but were more frequent and more intense in PCT and pseudoporphyria than in mEBA. Careful examination of direct immunofluorescence of mEBA vs. PCT and pseudoporphyria revealed different staining patterns, although overlapping features were present. Therefore, integrating all clinical and laboratory data is essential to differentiate between mEBA, PCT and pseudoporphyria.